Nutraceuticals as Potential Therapeutic Agents for Colon Cancer: A Review - Kuppusamy, Palaniselvam; M. M., Yusoff; Gaanty Pragas, Maniam; A. I., Solachuddin Jauhari; Soundharrajan, Ilavenil; Natanamurugaraj, Govindan (Elsevier Ltd., 2014)
Colon cancer is a world-wide health problem and the second-most dangerous type of cancer, affecting both men and women. The modern diet and lifestyles, with high meat consumption and excessive alcohol use, along with limited physical activity has led to an increasing mortality rate for colon cancer worldwide. As a result, there is a need to develop novel and environmentally benign drug therapies for colon cancer. Currently, nutraceuticals play an increasingly important role in the treatment of various chronic diseases such as colon cancer, diabetes and Alzheimer׳s disease. Nutraceuticals are derived from various natural sources such as medicinal plants, marine organisms, vegetables and fruits. Nutraceuticals have shown the potential to reduce the risk of colon cancer and slow its progression. These dietary substances target different molecular aspects of colon cancer development. Accordingly, this review briefly discusses the medicinal importance of nutraceuticals and their ability to reduce the risk of colorectal carcinogenesis.